2022
DOI: 10.1038/s41598-022-06101-1
|View full text |Cite
|
Sign up to set email alerts
|

Paper-based electrochemical immunosensor for label-free detection of multiple avian influenza virus antigens using flexible screen-printed carbon nanotube-polydimethylsiloxane electrodes

Abstract: Many studies have been conducted on measuring avian influenza viruses and their hemagglutinin (HA) antigens via electrochemical principles; most of these studies have used gold electrodes on ceramic, glass, or silicon substrates, and/or labeling for signal enhancement. Herein, we present a paper-based immunosensor for label-free measurement of multiple avian influenza virus (H5N1, H7N9, and H9N2) antigens using flexible screen-printed carbon nanotube-polydimethylsiloxane electrodes. These flexible electrodes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Similarly, the ePAD approach can be adopted to enhance the flexibility of voltammetric biosensors for multiplexed virus detection [ 88 ]. A screen-printed carbon electrode on paper substrate immunosensors has recently proven its stability in detecting multiple avian influenza viruses [ 89 ]. The biosensor measured the peak current decrease using DPV, achieving 55.7 pg mL −1 , 99.6 pg mL −1 , and 54.0 pg mL −1 LOD for avian influenza virus (AIV) H5N1, H7N9 and H9N2 hemagglutinin antigens with 20–30 min antibody-antigen binding time and only 10 of samples.…”
Section: Electrochemical Biosensors For Multi-virus Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the ePAD approach can be adopted to enhance the flexibility of voltammetric biosensors for multiplexed virus detection [ 88 ]. A screen-printed carbon electrode on paper substrate immunosensors has recently proven its stability in detecting multiple avian influenza viruses [ 89 ]. The biosensor measured the peak current decrease using DPV, achieving 55.7 pg mL −1 , 99.6 pg mL −1 , and 54.0 pg mL −1 LOD for avian influenza virus (AIV) H5N1, H7N9 and H9N2 hemagglutinin antigens with 20–30 min antibody-antigen binding time and only 10 of samples.…”
Section: Electrochemical Biosensors For Multi-virus Detectionmentioning
confidence: 99%
“… Peak current decrease under DPV measurement. 2 h AIV H5N1, H7N9, H9N2 antigens PBS AIV H5N1: 55.7 pg mL −1 (0.95 pM) AIV H7N9: 99.6 pg mL −1 (1.69 pM) AIV H9N2: 54.0 pg mL −1 (0.72 pM) 20–30 min No [ 89 ] Antibody Single working electrode. Peak current decrease under DPV measurement.…”
Section: Electrochemical Biosensors For Multi-virus Detectionmentioning
confidence: 99%
“…Wang et al also reported that the aptamer could provide an LOD in the range of 10 fM, whereas the antibody showed an LOD of 1 pM in detecting the influenza A virus. Using flexible and stable SP-CNT-polydimethylsiloxane electrodes, a paper-based immunosensor for the label-free hemagglutinin antigen (HA) detection of several AIVs (H5N1, H7N9, and H9N2) was demonstrated by Lee et al [ 43 ], whereby immune responses were measured via DPV. The LOD values for the different viruses were 55.7 pg/mL for H5N1 HA, 99.6 pg/mL for H7N9 HA, and 54.0 pg/mL for H9N2 HA.…”
Section: Cnts-based Biosensors For the Detection Of Human Virusesmentioning
confidence: 99%
“…The electrochemical-based biosensor has recently been advanced, providing a high signal-to-noise in analyte detection. This is accomplished by the developing various nanomaterials as the signal transducer [25][26][27][28] with its signal amplification strategy. [29,30] However, the complex composition of the electrode, starting from the signal transducer, advanced nanomaterial, and bioconjugation, mostly fails to be adapted for POC diagnostic tools for on-site biosensor.…”
Section: Introductionmentioning
confidence: 99%